2017
DOI: 10.18768/ijaedu.336258
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Undergraduate Efl Students’ Perceptions Towards Learning Together Strategy Implementation in an Efl Reading Comprehension Course

Abstract: The importance of reading comprehension proficiency in enhancing the academic success, development and growth of students' logical, intellectual, critical, emotional, social aspects and linguistic competencies is well documented. However, there is poor performance by Saudi EFL learners in reading comprehension section at both TOEFL and IELTS tests. This might be attributed to the negative perceptions Saudi EFL learners have towards reading comprehension instruction. These negative perceptions held by Saudi EFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
7
4
0
Order By: Relevance
“…The result indicated that the participants found collaborative dialogue fairly helpful in grasping key and supportive ideas of the texts. This finding is, to some extent, compatible with Elsayed and Fariza (2017), who reported that more than 85% of students agreed on the significance of collaboration in drawing their attention to key points in the text.…”
Section: Discussion Of the Results Related To The Second Research Quesupporting
confidence: 87%
See 4 more Smart Citations
“…The result indicated that the participants found collaborative dialogue fairly helpful in grasping key and supportive ideas of the texts. This finding is, to some extent, compatible with Elsayed and Fariza (2017), who reported that more than 85% of students agreed on the significance of collaboration in drawing their attention to key points in the text.…”
Section: Discussion Of the Results Related To The Second Research Quesupporting
confidence: 87%
“…Thus, the findings demonstrated that EFL students hold positive attitudes towards the dyadic collaborative dialogue they had in SCMC on their reading comprehension. This result agrees with the findings of the following studies that elicited the attitudes of EFL students toward collaborative approaches on their reading comprehension achievements: Al-Roomy (2013), Nejad and Keshavarzi (2015), Al-Jadoa (2016), Al-Qahtani (2016) and Elsayed and Fariza (2017). Rama et al (2018) and Teng (2015) went further by investigating student attitudes toward collaborative learning in SCMC as a prime means of their collaborative environment.…”
Section: Discussion Of the Results Related To The Second Research Quesupporting
confidence: 85%
See 3 more Smart Citations